2022
DOI: 10.1057/s41264-022-00183-8
|View full text |Cite
|
Sign up to set email alerts
|

Impact of financial literacy on financial well-being: a mediational role of financial self-efficacy

Abstract: The purpose of this paper is to explore the impact of financial literacy on financial well-being among the business school faculties. Both the variables (financial literacy and financial well-being) are operationalized as multi-dimensional constructs to undertake the study. Moreover, the paper also endeavored to examine the mediating role of financial self-efficacy between financial literacy and financial well-being. The paper adopts a survey by questionnaire method to gather data from 203 business school facu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(21 citation statements)
references
References 79 publications
(113 reference statements)
0
11
0
Order By: Relevance
“…The antecedents of FSE shape consumers' perceptions, thoughts, and beliefs about their financial capabilities and have a notable impact on the advancement and sustenance of the research field. Following a thorough review of the literature, we identified numerous predictors of FSE, including financial literacy (Brady et al, 2021; Herawati et al, 2020), financial knowledge (Salas‐Velasco, 2022), student loan literacy (Brady et al, 2021), financial awareness (Lone & Bhat, 2022; Mindra & Moya, 2017), financial experience (Hoffmann & Plotkina, 2021; Lone & Bhat, 2022), among others. In an ever‐evolving and complex financial landscape, financial literacy and self‐efficacy have emerged as essential skills for consumers to navigate economic challenges successfully (Herawati et al, 2020).…”
Section: Results Based On Tccm Frameworkmentioning
confidence: 99%
See 4 more Smart Citations
“…The antecedents of FSE shape consumers' perceptions, thoughts, and beliefs about their financial capabilities and have a notable impact on the advancement and sustenance of the research field. Following a thorough review of the literature, we identified numerous predictors of FSE, including financial literacy (Brady et al, 2021; Herawati et al, 2020), financial knowledge (Salas‐Velasco, 2022), student loan literacy (Brady et al, 2021), financial awareness (Lone & Bhat, 2022; Mindra & Moya, 2017), financial experience (Hoffmann & Plotkina, 2021; Lone & Bhat, 2022), among others. In an ever‐evolving and complex financial landscape, financial literacy and self‐efficacy have emerged as essential skills for consumers to navigate economic challenges successfully (Herawati et al, 2020).…”
Section: Results Based On Tccm Frameworkmentioning
confidence: 99%
“…Consumer Financial Protection Bureau (CFPB) (2015) defines FWB as “a state of being wherein a person can fully meet current and ongoing financial obligations, can feel secure in their financial future, and is able to make choices that allow them to enjoy life.” However, the literature provides limited insights regarding the causal relationship between FSE and FWB. Despite this, a limited number of studies (Lone & Bhat, 2022; Oquaye et al, 2022) have explored the association between FSE and FWB, indicating a positive relationship between the two constructs. Brüggen et al (2017) conducted a comprehensive study that expounds on the intricate and dynamic construct framework of FWB.…”
Section: Results Based On Tccm Frameworkmentioning
confidence: 99%
See 3 more Smart Citations